PERAN CONVENTION ON INTERNATIOAL TRADE IN ENDANGERED SPECIES OF WILD FAUNA AND FLORA (CITES) DALAM MENDUKUNG SUSTAINABLE DEVELOPMENT GOALS (SDGS TUJUAN 15 POIN 7) DI INDONESIA PERIODE 2015-2017 - Cathrine Anggia Riani (2022)
ABSTRACT The increasing trend that occurred related to illegal trade cases in Indonesia in 2015-2017 became a separate concern to be resolved immediately. The presence of CITES as an international convention that has been present since 1973 has not been able to guarantee the survival of protected plants and animals so that its role as an international regime is doubted, especially in supporting one of the SDGS goals which is in line with the goals of CITES itself. Departing from the presence of CITES, it has an important role in controlling and monitoring the trade in protected wild plants and animals as a form of support for SDGS, especially in Indonesia. This research has a purpose, namely to find out the role of CITES as an international convention that focuses on trade in protected animals and plants as a form of support for achieving SDGS goal 15 which focuses on point 7 in Indonesia and to understand more deeply about the trade in protected animals in Indonesia which is seen from the role CITES also sees SDGS goal 15 point 7 as a hope in fighting the crime of illegal animal trade. This study uses a qualitative approach with research methods that begin with data collection in the form of secondary data which is then analyzed. The research framework used is the international regime and also sustainable development. The results of this study are that the correct role of CITES in supporting the success of the SDGS goals still does not guarantee the achievement of resolving the scarcity of animals and plants due to illegal trade because there is still one indicator that greatly influences its success, namely the weak commitment of the state in overcoming the scarcity of wildlife due to illegal trade. Keywords: Illegal Trade, CITES, Role of international regimes, international conventions, sustainable development, SDGS, Indonesia